Substitution in Ayurveda w.s.r to Yogratnakar : A Conceptual Study - Rathore, Poonam; Bhagat, Seema (International Research Journal of Ayurveda & Yoga, 2022)
Introduction- Substitution is a replacement of equivalent drugs in place of original drugs on the basis of similar pharmacological actions and therapeutic uses. In Ayurveda, substitution is described by the name of Abhava Pratinidhi Dravya. During Samhita Kala, concept of substitution was not existed but later on this practices come in existence, but Acharya Vagbhata has mentioned that the Dravya having similar Rasa (Taste), Guna (Property), Virya (Potency) and Vipaka (Bio transformation) should be used in absence of each other. Material and Methods- Thorough review of Ayurvedic literature related to Abhava Pratinidhi Dravya is done for the better understanding of the concept, Ayurveda Compendia, Journals and Publications. Result & Discussion- Substitution provides a great scope for the physician to utilize drugs that are easily available, cost effective and most appropriate for the management of the diseases. Now a days, the concept of substitution is entirely converted into intentional and unintentional malpractices of adulteration. This study mainly focuses on the concept of substitution with special reference to Yogratnakar in which commonly used substitute in place of original drug like Trianthema portulacastrum (Varshabhu) in place of Punarnava (Boerhavia diffusa), Chitrak ( Plumbago zelenycum) for Danti ( Baliospermum montanum). Polylthia longifolia for Ashoka (Saraca indica). etc has been delimeated.